Characterization of the superconcentration and granulation steps of a disruptive spray-drying free process for the manufacture of dairy powders. (March 2022) - Patil, Maheshchandra H.; Murphy, Eoin G.; Tanguy, Gaëlle; Le Floch-Fouéré, Cécile; Jeantet, Romain
Abstract: Breakthrough energy savings were recently projected by a spray-dryer free dairy powder manufacturing process based on superconcentration and granulation. The extent of superconcentration and the recirculation rate of powder for granulation, determines process performance. In this study, the evolution of physical properties during superconcentration and granulation was investigated for a model system (skim milk microfiltrate) using rheological and shear-cell based techniques. Results demonstrated that superconcentration leads to the development of a cohesive non-flowing state. The transition from concentrate to cohesive wet powder regime, manifested as a sharp increase in cohesiveness, occurring at around 82% w/w dry matter (DM). Powder addition for successful granulation was related to DM at the end of the cohesive phase (∼89% w/w DM). Interestingly, laboratory-based rheological and shear cell measurements were well correlated with the amperage of the mixer used; similar measurements could be applied in-process providing a better understanding and control of the product behavior within the system. Highlights: Flow behavior of dairy superconcentrates was successfully modelled. Onset of a highly cohesive phase restricts superconcentration processes. Shear-cell based tests provide critical information about cohesive phase. Agitator power consumption reliably reflects evolution in product flow behavior.